Middle Rio Grande Conservation Action Plan: framework and status assessment: final report - Muldavin, Esteban, author; Milford, Elizabeth, author; Grunau, Lee, author; Rondeau, Renée, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2015)
The Middle Rio Grande Conservancy District, as part of it stewardship of the natural habitats of the Middle Rio Grande corridor, has initiated a conservation action planning process. We report here on the first steps of the process: developing an ecologically based framework for stewardship, identifying conservation targets, and providing an initial assessment of their current and desirable future status based on measureable indicators. Additionally, major threats or stressors to the conservation targets are identified and evaluated with respect to the severity of their potential impacts. The overall goal of the planning process is to provide a foundation for developing strategies that can be applied to meet conservation goals in collaboration with the Middle Rio Grande Conservancy District's many partners and stakeholders.
Apr-15
Keywords: dynamic patch mosaic; MRG-CAP; conservation; riparian communities; wetland vegetation communities; habitats; critical threats; stewardship